Appraisal - Who needs it? - THULASIDAS, M. (Institutional Knowledge at Singapore Management University, 2007)
WE GO through this ordeal every year when our boss- es appraise our performance. Our career progression, bonus and salary depend on it. So, we spend sleepless nights agonising over it.